Justice for All : Promoting Social Equity in Public Administration. - Norman J. Johnson; James H. Svara (M.E. Sharpe, Inc., 2011)
Justice for All is the first book that provides a comprehensive examination of social equity in American public administration. The breadth of coverage--theory, context, history, implications in policy studies, applications to practice, and an action agernda--cannot be found anywhere else.